Expanding the Application of the African Centered Paradigm Model, Use of Its Social Components as Tools in the Provision of Mobile HIV AIDS Outreach with Transgender Dropout Youth and Adults, Expanding the Empirical Study - Nancy E. Jackson (Adult Education Research Conference, 2010)
In this session we will explore adapting some of the social components of the African centered paradigm as tools to improve the provision of street outreach services to African American male and female and transgendered sex workers targeted for positive health and well being messages, HIV and AIDS Education, Testing and informal counseling in a mobile camper setting.